EFFECTS OF CATION TREATMENT ON BODY - ORGAN WEIGHT RATIO AND PATHOPHYSIOLOGICAL CHANGES IN PERITONEUM CAVITY OF FEMALE NEW ZEALAND RABBITS - Ifeanyi, Ojiezeh Tony; Jack, Okoko Fabian; Victor, Emojevwe (European Scientific Journal, ESJ, 2014)
The role of trace elements in normal function of the body cannot be over emphases. This study was carried out to determine the effects of oral administration of zinc (Zn2+), copper (Cu2+) and magnesium (Mg2+) on body, organ weight and pathophysiological changes in the peritoneum of New Zealand White rabbits. Standard solutions of the cationic salts were prepared using sterile distilled water to obtain two concentration of each cation. The rabbits were distributed into seven groups: Group I was administered 10.00 μg / ml of Mg2+, Group II received 20.00 μg / ml of Mg2+, Group III received 16.00 μg / ml of Zn2+, Group IV received 32.00 μg / ml of Zn2+, Group V received 2.00 μg / ml of Cu2+, Group VI received 4.00 μg / ml of Cu2+ while, group VII were left untreated with any cation supplement. The increase in body, and organ weights in the rabbits treated the cations was concentration dependent in Zn2+ supplemented group (P > 0.05), but not in Cu2+ and Mg2+ groups. The increment in mean body – organ ratio of treated rabbits was statistically significant (P < 0.05) when compared with untreated rabbits. Mg2+ showed more fat deposit followed by Cu2+ groups but none in Zn2+ groups. It was therefore, concluded that oral supplements of copper, zinc and magnesium caused changes in body weight and weight of organs of spleen, liver, lungs, kidneys and ovaries. The excess fat deposit around some of the internal organs may impede it normal physiological function.